The Greater the Tilt, the Taller the Nest? The Effect of Solar Array Type on Bird Nest Architecture and Nest Microclimate - Brendan Enochs; Adrianna Burghardt; Amy Friemoth; Chelse Prather (Ecology and Evolution, 2025)
ABSTRACT The increasing demand for renewable energy has led to widespread installation of photovoltaic (PV) solar arrays, however, their ecological impacts, particularly on bird species, remain poorly understood. This study investigates robin nesting behavior within fixed and tracking solar arrays in Dayton, Ohio, with a focus on species presence, nest architecture modifications, and thermal conditions. We found American robin (Turdus migratorius), House finch (Haemorhous mexicanus), and House sparrow (Passer domesticus) nests across two sites: a tracking array and a fixed array. Results showed that robin nests in the tracking array exhibited significant architectural adaptations, including taller nests and greater variability in attachment angles, likely to enhance stability as panels moved throughout the day. Additionally, nests in tracking arrays experienced warmer thermal conditions than those in fixed arrays. These findings suggest that generalist bird species can adapt to nesting in dynamic, human‐modified environments, modifying their nests to cope with structural movement and thermal changes. The study contributes to understanding bird ecology in solar arrays and provides insights for integrating wildlife considerations into solar energy designs.